Effective Passivation of Large Area Black Silicon Solar Cells by SiO2/SiNx:H Stacks. (6th March 2014) - Zhao, Zengchao; Zhang, Bingye; Li, Ping; Guo, Wan; Liu, Aimin
Abstract : The performance of black silicon solar cells with various passivation films was characterized. Large area (156 × 156  mm 2 ) black silicon was prepared by silver-nanoparticle-assisted etching on pyramidal silicon wafer. The conversion efficiency of black silicon solar cell without passivation is 13.8%. For the SiO2 and SiN x :H passivation, the conversion efficiency of black silicon solar cells increases to 16.1% and 16.5%, respectively. Compared to the single film of surface passivation of black silicon solar cells, the SiO2 /SiN x :H stacks exhibit the highest efficiency of 17.1%. The investigation of internal quantum efficiency (IQE) suggests that the SiO2 /SiN x :H stacks films decrease the Auger recombination through reducing the surface doping concentration and surface state density of the Si/SiO2 interface, and SiN x :H layer suppresses the Shockley-Read-Hall (SRH) recombination in the black silicon solar cell, which yields the best electrical performance of b-Si solar cells.